2018
DOI: 10.1037/ocp0000107
|View full text |Cite
|
Sign up to set email alerts
|

The more, the better? Curvilinear effects of job autonomy on well-being from vitamin model and PE-fit theory perspectives.

Abstract: In organizational psychology research, autonomy is generally seen as a job resource with a monotone positive relationship with desired occupational outcomes such as well-being. However, both Warr's vitamin model and person-environment (PE) fit theory suggest that negative outcomes may result from excesses of some job resources, including autonomy. Thus, the current studies used survey methodology to explore cross-sectional relationships between environmental autonomy, person-environment autonomy (mis)fit, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 65 publications
9
79
0
Order By: Relevance
“…In addition, empirical studies showed that an excess of autonomy seems to have negative effects on employee well-being (Stiglbauer & Kovacs, 2018;Wielenga-Meijer et al, 2011).…”
Section: Challenge and Hindrance Job Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, empirical studies showed that an excess of autonomy seems to have negative effects on employee well-being (Stiglbauer & Kovacs, 2018;Wielenga-Meijer et al, 2011).…”
Section: Challenge and Hindrance Job Characteristicsmentioning
confidence: 99%
“…Consequently, researchers have begun to argue that (a) not all demands are created equal and (b) job resources can have detrimental effects as well (Stiglbauer & Kovacs, 2018;Wielenga-Meijer et al, 2011).…”
Section: Challenge and Hindrance Job Characteristicsmentioning
confidence: 99%
“…There is a strong correlation between education and job control, with increasing educational levels associated with higher job control [78,79]. Some studies have suggested that there are non-linear associations between influence at work and well-being, and that more influence may no longer be associated with better well-being at the highest levels [80]. It is possible, that such non-linearity may explain that the associations in the present study were limited to lower educational levels.…”
Section: Differences In the Associations Between Job Control And Deprmentioning
confidence: 53%
“…Taken together, it seems that the beneficial role of global autonomy in working life has become less evident, while information processing and the project-type nature of current jobs has highlighted the importance of mutual interdependencies and time-synchronies in autonomous work. However, most previous research has focused on global job autonomy using predefined quantitative scales without intending to analyze the ambivalence or psychological burden arising from the tension between autonomous status and strong temporal/social interdependence (Parker et al 2014;Stiglbauer and Kovacs 2018). It seems likely that this tension can cause feelings of insufficiency and stress (Mazmanian et al 2013).…”
Section: Autonomy Temporal Conditions and Well-beingmentioning
confidence: 99%
“…Interrelatedness and Autonomy in Knowledge Work Several influential models of occupational stress and well-being have defined work autonomy as a central factor (e.g., Carayon 1993;Demerouti et al 2001;Frese 1989;Hackman andOldham 1975, Karasek Jr. 1979). In these models, autonomy is assumed to have the potential to ensure motivation and performance as well as well-being (Stiglbauer and Kovacs 2018). Most of these frameworks were developed during the era of a strong industrial sector and when rather pre-structured office jobs were increasing in Western countries.…”
Section: Introductionmentioning
confidence: 99%